The gift of giving - Lynberg, Michael (New York Fawcett Columbine, 1991)
Drawing on the wise and practical advice of the great philosophers and spiritual leaders of all ages--from Socrates to Shakespear, from Martin Luther King, Jr. to Mother Teresa-The Gift of Giving helps you discover what you can do to make your life more meaningful and fulfilling.
D., 4/5/2006, E Violette
Keywords: Life